Chapter Membrane Dynamics of Spermatozoa during Capacitation: New Insight in Germ Cells Signalling - Ramal Sanchez, Marina (InTechOpen, 2018)
The study of germline stem cells and of germline cells has deep implications for the understanding of fertility, development and cancer. Nowadays, we are experiencing the very fascinating challenge of application of -OMICS technologies to this issue, which is opening new and unexpected horizons in virtually all the branches of biology. Here, we carried out a review of signalling systems involved in maturation of male germ cells and in the process that leads them to become fully fertile. In particular, we discuss the control mechanisms involved in capacitation and acrosome reaction that act at membrane level. Indeed, spermatozoa membranes play key roles in determining the achievement of fertility: they are the interface with the surrounding environment, they locate the signal transduction systems and they are active in recognizing and binding the oocyte. In addition, we discuss the effect of several compounds that could exert a negative effect on reproductive activity, by interfering with the endocrine axis, the so-called endocrine disruptors.